Exploring Character Education and Anti-Racism in Abdoel Moeis’s Novels and Joseph Conrad’s “Heart of Darkness”: A Comparative Literary Analysis - Nushashikin Nushashikin; Nurizzati Nurizzati; Yenni Hayati (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this research is to describe the racial discrimination found in the first and second novels, to describe the similarities and differences of racial discrimination found in both novels and the application of character education values without racial discrimination. The type of research used is qualitative research using a comparative descriptive method. The data in this study are sentences that contain forms of discrimination. Sentences that contain racial discrimination are obtained through the utterances or utterances of the narrator, the utterances or utterances of the characters, and the actions of the characters in both novels. Data collection techniques using reading and note techniques. The data validation technique uses triangulation techniques. Data analysis techniques using descriptive techniques. The results of the study show that both novels have similarities and differences, there are three kinds of discrimination, namely ethnocentrism discrimination (attitudes comparing cultures), xenophobic discrimination (hate and dislike), stereotype discrimination (generalizing attitudes towards a group). The similarities between these two novels are the setting in which racial discrimination occurred during the colonial era and the victims of racial discrimination, namely the natives themselves. The difference between the two novels is the setting where racial discrimination occurs. The setting in the first novel is Indonesia, while the setting in the second novel is Congo, Africa. Based on the results of data analysis and discussion found 26 data.